Crime and tourist arrivals: Is there any relationship? - Thian, Li Shya (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The main purpose of this study is to investigate the dynamic relationship between crimes (Total Crime, Thefts and Other Stealing, Robbery and Extortion, Burglary, House and Store Breaking, Arson, Murder and Manslaughter, and Assaults) and tourist arrivals in Sarawak. This study covered the annual data from 1970 to 2009. The stationary properties of the time series data are examined by using Augmented Dickey- Fuller (ADF) test, Philips and Perron (PP) test and Kwiatkowski-Philips-Schmidt-Shin (KPSS) test. The Johansen and Juselius cointegration and vector error correction model (VECM) were applied to find out long run relationship along with causality among the variables, whereas vector autoregression (V AR) Granger causality test were applied to find out the short run causality among the variables. The results provide evidence ofthe .,' existence oflong run co integration relationship among Arson, Murder and Manslaughter with tourist arrivals, but no causality, relationships were detected between these two variables. For the other five variables, the results showed that the unidirectional Granger causality running from tourist arrivals to Total Crime, and Burglary, House and Store Breaking, but no causal relationships between the Thefts and Other Stealing, Robbery and Extortion, and Assaults were detected.